Approaches, methods and methodologies in teaching visual arts according to Chat GPT (Revista Apotheke, 2025)
This article presents questions asked to Chat GPT (Generative Pre-trained Transformer) and answers generated by it using Artificial Intelligence (AI). All questions written in the chat prompt address the topic of this article. The initial questions are more comprehensive, focused on approaches, methods and methodologies for teaching in general that are gradually directed towards the teaching of visual arts. Because of this, it is around the Triangular Approach to Teaching and Learning Art in Brazil systematized by Ana Mae Barbosa that the following questions are structured. Thus, relations of this approach with decoloniality, Paulo Freire, reinterpretation in the visual arts, generative art and AI constitute the final questions. We chose to publish the answers obtained in full with footnotes, in case any term or concept requires specific understanding. Finally, our critical analysis of the questions and answers that make up this article are presented in the conclusion.
Keywords: approach; methods and methodologies; teaching visual arts; chat GPT; artificial intelligence